Виды родов Botrydium Wallroth и Vaucheria De Candolle (Xanthophyceae) юга Прибайкалья (Россия) - Вишняков, В.С. (Альгология, 2018)
Исследованы сифональные желтозеленые водоросли (Xanthophyceae) на юге Прибайкалья (2011—2017 гг.). В 218 местонахождениях найдено 375 популяций 15 таксонов из родов Botrydium (1 вид) и Vaucheria (13 видов и 1 разновидность). Botrydium granulatum (Linnaeus) Greville отмечен однажды. The yellow green algae belonging to the genera Botrydium and Vaucheria (Xanthophyceae) were studied in the south of the Baikal region from 2011 to 2017. As a result, 375 populations of 15 siphonous xanthophytes from Botrydium (1 species) and Vaucheria (13 species and 1 variety) have been revealed in the 218 localities of the studied region. Botrydium granulatum (Linnaeus) Greville was recorded only once while 374 populations represented the taxa from genus Vaucheria.